Mortality from abdominal aortic aneurysm: trends in European Union 15+ countries from 1990 to 2017. Issue 11 (11th May 2020) - Al‐Balah, A.; Goodall, R.; Salciccioli, J. D.; Marshall, D. C.; Shalhoub, J.
Abstract : Background: This observational study assessed trends in abdominal aortic aneurysm (AAA) death rates in European Union (EU) 15+ countries for the years 1990 to 2017. Methods: Age‐standardized death rates (ASDRs) were extracted from the Global Burden of Disease Study Global Health Data Exchange. Trends were analysed using joinpoint regression analysis. Results: Between 1990 and 2017, ASDRs from AAA decreased in all 19 EU15+ countries for women, and in 18 of 19 countries for men. Increasing AAA mortality was observed only for men in Greece (+5·3 per cent). The largest relative decreases in ASDR between 1990 and 2017 were observed in Australia (men –65·6 per cent, women –50·4 per cent) and Canada (men –60·8 per cent, women –48·6 per cent). Over the 28‐year interval, the smallest decreases in ASDR for women were noted in Greece (–2·3 per cent) and in Italy (–2·5 per cent). In 2017, the highest mortality rates were observed in the UK for both men and women (7·5 per 100 000 and 3·7 per 100 000 respectively). The lowest ASDR was observed in Portugal for men (2·8 per 100 000) and in Spain for women (1·0 per 100 000). ASDRs for AAA in 2017 were higher for men than women in all 19 EU15+ countries. The most recent trends demonstrated increasing AAA ASDRs in 14 of 19 countries for both sexes; the increases were relatively small compared with the improvements in the preceding years. Conclusion: This observational study identified decreasing mortality from AAA across EU15+ countries since 1990. The most recent trends demonstrated relatively small increases in AAA mortality across the majority of EU15+ countries since 2012. Abstract : This observational study outlined trends in abdominal aortic aneurysm mortality in EU15+ countries from 1990 to 2017. Overall, there has been a decrease in mortality. generally improving picture Abstract : Antecedentes: Este estudio observacional evalúa las tendencias en las tasas de mortalidad del aneurisma de aorta abdominal ( abdominal aortic aneurysm, AAA) en los 19 países integrantes del acrónimo conocido como EU15+ en los aóos 1990‐2017. Métodos: Se obtuvieron las tasas de mortalidad estandarizadas por la edad del Global Burden of Disease Study Global Health Data Exchange. Las tendencias se analizaron utilizando el análisis de regresión por puntos de inflexión (joinpoint). Resultados: Entre 1990 y 2017, las tasas de muerte estandarizadas por edad ( age‐standardized death rates, ASDR) del AAA disminuyeron en todos los 19 EU15+ países para las mujeres, y en 18 de los 19 países para los varones. Solamente se observó un incremento de la mortalidad del AAA para los varones en Grecia (+5, 3%). El mayor descenso relativo de ASDR entre 1990‐2017 se observó en Australia (varones ‐65, 6%, mujeres ‐50, 4%) y Canadá (varones ‐60, 8%, mujeres ‐48, 6%). A lo largo del periodo de 28 aóos, en el caso de las mujeres, los menores descensos en ASDR se observaron en Grecia (‐2, 3%) y en Italia (‐2, 5%). En 2017, las tasas de mortalidad más elevadas se observaron en el Reino Unido tanto para varones como para mujeres (7, 5/100.000 y 3, 7/100.000 para varones y mujeres, respectivamente). La ASDR más baja se observó en Portugal para varones (2, 8/100.000) y Espaóa para mujeres (1, 0/100.000). Las ASDRs para AAA en 2017 fueron más altas para varones que para mujeres en todos los 19 países EU15+. Las tendencias más recientes demostraron aumentos de las ASDRs por AAA en 14 de 19 países para varones y mujeres; los aumentos fueron relativamente pequeóos cuando se compararon con las mejorías observadas dentro de los aóos precedentes. Conclusión: En este estudio observacional de los países EU15+, se ha identificado una disminución en la mortalidad de los AAA entre los países integrantes de EU15+ desde 1990. Las tendencias más recientes demuestran aumentos relativamente pequeóos de la mortalidad del AAA en la mayoría de los países EU15+ desde 2012.